Monovacant polyoxometalates incorporated into MIL-101(Cr): novel heterogeneous catalysts for liquid phase oxidation - Granadeiro, Carlos M.
Two novel hybrid composite materials, PW11@MIL-101 and SiW11@MIL-101, were prepared by the inclusion of the potassium salts of the monovacant polyoxotungstates, [PM11O39](7-) (PW11) and [SiW11O39](8-), into the porous Metal-Organic Framework MIL-101(Cr). Materials were characterized by a myriad of solid-state methods such as powder X-ray diffraction (XRD), vibrational (FT-IR and FT-Raman) and P-31 solid-state NMR spectroscopies, elemental analysis, scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX), and textural analysis confirming the incorporation of the POMs into MIL-101(Cr). PW11@MIL-101 and SiW11@MIL-101 revealed to be active, selective and recyclable catalysts for the oxidation of cis-cyclooctene, geraniol and R-(+)-limonene using the H2O2 as oxidant Only one product was obtained from the epoxidation of cis-cyclooctene and geraniol: 1,2-epoxycylooctane and 2,3-epoxygeraniol, respectively. In the oxidation of R-(+)-limonene the main products were limonene-1,2-epoxide and limonene-1,2-diol, however the diepoxide was also formed. Both composite materials, PW11@MIL-101 and SiW11@MIL-101, are recyclable for, at least, three consecutive cycles without significant loss of activity. The stability of the composites after the catalytic cycles was confirmed by several techniques. Remarkably, the MOF framework was found to play an important role in the stability of the PW11 in the presence of H2O2. (C) 2013 Elsevier B.V. All rights reserved.